SAT0046 MODIFIED DISEASE ACTIVITY SCORE AT 3 MONTHS IS A SIGNIFICANT PREDICTOR FOR RAPID RADIOGRAPHIC PROGRESSION AT 12 MONTHS COMPARED WITH OTHER MEASURES. (2nd June 2020) - Movahedi, M.; Weber, D.; Akhavan, P.; Keystone, E.
Abstract : Background: Progressive rheumatoid arthritis (RA) is responsible for joint damage causing disabilities with no agreement on which disease measures best predict radiographic progression Objectives: We aimed to determine which disease activity measures including disease activity score (DAS), modified (M) DAS28 (CRP), clinical disease activity index (CDAI), and health assessment questionnaire disability index (HAQ-DI) best predict rapid radiographic progression (RRP) in early RA patients at baseline (BL) and 3 months. Methods: PREMIER data, a 2-year, multicenter, double-blind active comparator–controlled study with methotrexate (MTX) naïve RA patients and active disease <3 years, were used. Only patients in the MTX arm were analyzed. RRP was defined as change in modified total Sharp (mTSS) > 3.5 at month 12. Logistic regression analysis assessed impact of measures at BL and 3 months on RRP at 12 months. Best cut-off points of M-DAS28(CRP) was also estimated using area under the receiver operating characteristic curve. Results: 149 patients were included: female (n=113; 75.8%), positive RF (n=127; 85.2%), mean (SD) age 52.9 (13.3) years, disease duration 0.8 (0.9) year, DAS28(CRP) 6.3 (0.9). After adjusting for potential confounders, only M-DAS28(CRP) at BL (adj OR=3.29; 95% CI: 1.70-6.36) and 3 months (adj OR=2.56; 95% CI: 1.43-4.56) strongly predicted RRP at 12 months. M-DAS28(CRP) 4.5 and 2.6 at BL and 3 months maximized sensitivity and specificity for prediction of RRP. Conclusion: M-DAS28(CRP) was a stronger predictor at BL and 3 months for RRP compared with other disease activity measures. Removing tender joint count and patient global assessment from DAS28(CRP) improves prediction of RRP. References: [1] Breedveld FC, Weisman MH, Kavanaugh AF, Cohen SB, Pavelka K, van Vollenhoven R, et al. The PREMIER study: A multicenter, randomized, double-blind clinical trial of combination therapy with adalimumab plus methotrexate versus methotrexate alone or adalimumab alone in patients with early, aggressive rheumatoid arthritis who had not had previous methotrexate treatment. Arthritis and rheumatism. 2006;54(1):26-37. Acknowledgments: The authors wish to knowledge AbbVie Canada Inc. for providing patients data. Disclosure of Interests: Mohammad Movahedi Consultant of: Allergan, Deborah Weber: None declared, Pooneh Akhavan: None declared, Edward Keystone Grant/research support from: AbbVie; Amgen; Gilead Sciences, Inc; Lilly Pharmaceuticals; Merck; Pfizer Pharmaceuticals; PuraPharm; Sanofi, Consultant of: AbbVie; Amgen; AstraZeneca Pharma; Bristol-Myers Squibb Company; Celltrion; F. Hoffman-La Roche Ltd.; Genentech, Inc; Gilead Sciences, Inc.; Janssen, Inc; Lilly Pharmaceuticals; Merck; Myriad Autoimmune; Pfizer Pharmaceuticals, Sandoz, Sanofi-Genzyme, Samsung Bioepsis., Speakers bureau: AbbVie; Amgen; Bristol-Myers Squibb; Celltrion; F. Hoffman-La Roche Ltd, Janssen, Inc; Merck; Pfizer Pharmaceuticals; Sanofi-Genzyme; UCB